Energy Metabolism in Osteogenic Differentiation and Reprogramming: A Possible Future Strategy for Periodontal Regeneration - Fujihara, Chiharu; Nantakeeratipat, Teerachate; Murakami, Shinya (Frontiers in Dental Medicine, 2022)
Energy metabolism is crucial in stem cells as they harbor various metabolic pathways depending on their developmental stages. Moreover, understanding the control of their self-renewal or differentiation via manipulation of their metabolic state may yield novel regenerative therapies. Periodontal ligament (PDL) cells existing between the tooth and alveolar bone are crucial for maintaining homeostasis in the periodontal tissue. In addition, they play a pivotal role in periodontal regeneration, as they possess the properties of mesenchymal stem cells and are capable of differentiating into osteogenic cells. Despite these abilities, the treatment outcome of periodontal regenerative therapy remains unpredictable because the biological aspects of PDL cells and the mechanisms of their differentiation remain unclear. Recent studies have revealed that metabolism and factors affecting metabolic pathways are involved in the differentiation of PDL cells. Furthermore, understanding the metabolic profile of PDL cells could be crucial in manipulating the differentiation of PDL cells. In this review, first we discuss the energy metabolism in osteoblasts and stem cells to understand the metabolism of PDL cells. Next, we summarize the metabolic preferences of PDL cells during their maintenance and cytodifferentiation. The perspectives discussed have potential applicability for creating a platform for reliable regenerative therapies for periodontal tissue.